2016
DOI: 10.1016/j.srhc.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Leisure time physical activity among pregnant women and its associations with maternal characteristics and pregnancy outcomes

Abstract: Positively, a considerably high proportion of Swedish pregnant women achieved the recommended level of physical activity. Factors associated with recommended physical activity level were BMI ≤30 kg/m(2), very good or good self-rated health, and higher educational level. Our findings emphasize the need for health care professionals to early detect and promote fertile and pregnant women towards health-enhancing physical activity, especially those with low levels of physical activity and overweight/obesity, to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 29 publications
4
25
1
1
Order By: Relevance
“…Studies using lab-based techniques such as DXA and densitometry have likewise reported lower fat mass and body fat percentage in babies born to women who were more active during pregnancy [51,52]. In line with other largescale population-based studies [53,54] and smaller studies incorporating accelerometry [55], we found no indication that physical activity adversely affected gestational age or birth weight. Recent meta-analyses indicate that leisure-time physical activity may be advantageous in reducing the risk of pre-term deliveries [9,10] and large-for-gestational age births [10][11][12].…”
Section: Neonatal Delivery Outcomes and Body Compositionsupporting
confidence: 87%
“…Studies using lab-based techniques such as DXA and densitometry have likewise reported lower fat mass and body fat percentage in babies born to women who were more active during pregnancy [51,52]. In line with other largescale population-based studies [53,54] and smaller studies incorporating accelerometry [55], we found no indication that physical activity adversely affected gestational age or birth weight. Recent meta-analyses indicate that leisure-time physical activity may be advantageous in reducing the risk of pre-term deliveries [9,10] and large-for-gestational age births [10][11][12].…”
Section: Neonatal Delivery Outcomes and Body Compositionsupporting
confidence: 87%
“…Inadequate knowledge of nutritional principles can result in many dietary errors, which may result in an excess or deficiency of energy and specific nutrients that are important for the successful course of a pregnancy and a child’s healthy development [26,27]. Good nutrition, combined with appropriate physical activity and avoidance of bad habits, increases the likelihood that the course of the pregnancy will follow an optimal course [28,29]. …”
Section: Introductionmentioning
confidence: 99%
“…As the pregnancy progresses, the relatively rapid weight gain, combined with endocrine changes and mood fluctuations, cause the woman to limit her daily physical activity [2,3]. This may sometimes lead to total akinesia [4], the consequences of which have been proven to have a more negative effect in pregnant than in non-pregnant women [5]. Physical activity improves cardiovascular and respiratory functions and enhances metabolic mechanisms.…”
Section: Introductionmentioning
confidence: 99%